"Do I still have epilepsy?" Epilepsy identity 15–20 years after anterior temporal lobectomy. Issue 2 (4th December 2021) - Coleman, Honor; McIntosh, Anne; Wilson, Sarah J.
Abstract: Objective: Identity is a multifaceted construct, comprising personal identity (sense of being a unique individual) and social identity (the sense‐of‐self derived from membership of social groups). Social identity involves explicit identification with a group ("I am …") and implicit behaviors or attitudes associated with group membership. Following successful treatment with surgery, patients with epilepsy can undergo a complex and lasting change in personal identity. To date, there has been no research into postoperative social epilepsy identity (SEI). We sought to examine SEI 15–20 years post‐surgery, and the relationship between SEI and satisfaction with surgery, psychosocial improvements, mood, and health‐related quality of life (HRQoL). Methods: Thirty‐two patients who underwent anterior temporal lobectomy (ATL; 19 female) were recruited, with a median follow‐up of 18 years (interquartile range [IQR] = 2.5). Using a novel interactive online program, we collected data on SEI, satisfaction with surgery, and perceived psychosocial improvements, alongside standardized measures of mood (Neurological Disorders Depressio Inventory‐Epilepsy; Patient Health Questionnaire‐Generalised Anxiety Disorder‐7 item) and HRQoL (Quality of Life in Epilepsy‐31 item). Non‐parametric analyses were used to analyse the data. Results: Twenty‐five percent of patients were free of disabling seizures since surgery, yet 65% stated they no longer had epilepsy and >90% reported satisfaction with surgery. Explicitly discarding SEI was positively associated with HRQoL at long‐term follow‐up, over and above seizure outcome. Implicit SEI was expressed as (a) acceptance of epilepsy, (b) a sense of belonging to the epilepsy community, and (c) difficulty disclosing and discussing epilepsy. Difficulty disclosing and discussing epilepsy was associated with increased anxiety and lower HRQoL. Significance: At long‐term follow‐up, over half of our patients reported an explicit change in SEI, which could promote better HRQoL. In contrast, difficulty with disclosure of epilepsy was associated with increased anxiety and reduced HRQoL, possibly reflecting the ongoing effects of stigma. These findings highlight the importance of understanding changes in patient social identity for promoting long‐term well‐being after surgery.